(untitled) (Academia Journal of Medicine, 2020)
Background: Atherosclerotic cardiovascular disease (ASCVD) is the leading cause of death universally. The present study was conducted to assess LA volume index (LAVI) in the patients with ACS in adults. Subjects and Methods: The present study was conducted on120 adult patients diagnosed with ACS of both genders in narayana medical college hospital from May 2016 toOctober 2016. Patients were divided into 2 groups of 60 each. Group I patients had LAVI > 34 ml/m2and group II patients had LAVI ≤ 34 ml/m2. The LV systolic function was analyzed by Simpson’s disc volumetric method. The LAV was assessed by the biplane area-length method from apical 4-chamber and 2-chamber views. Results: The mean BMI in group I patients was 26.7 kg/m2and in group II was 26.1 kg/m2, AW STEMI in group I was seen in 30 patients and in group II in 32, IW + PW STEMI in 6 and 4 patients in both groups respectively, IW STEMI in 5 and 4 patients respectively, NSTEMI in 4 and 3 patients respectively and UA in 15 and 17 patients respectively. Risk factors were diabetes mellitus in 32 and 27 patients respectively, hypertension in 41 and 40 patients respectively, smoking in 43 and 38 patients respectively, alcohol in 30 and 35 patients respectively and positive family history in 12 and 16 patients respectively. The difference was non- significant (P> 0.05). The mean LAVI at admission in group I was 38.1 and in group II was 27.2, after 1 month was 40.2 and 28.1 in both groups, after 6 months was 39.1 and 27.9 in both groups and after 12 months was 42.7 and 25.3 in both groups respectively. The difference was significant (P<0.05). Conclusion: Authors conclude that LAVI was found to be the independent predictor of mortality than left ventricular ejection fraction on multivariate regression analysis. Common risk factors in patients with ACS were diabetes mellitus, hypertension, smoking, alcoholism and positive family history. Patients with LAVI of value >34 ml/m2 were associated with increased comorbidities.